Manajemen nasehat nutrisi dalam praktek dokter gigi Management of nutrition advised in dentist practice - Rosa Amalia (DiscoverSys Inc., 2011)
The evidence of relation between nutrition and oral health has addressed nutrition issues on a new urgency indental practices as a part of efforts in developing quality of care. Nutrition is a modifiable factors and could beadviced to patients that ensure progression and maintainance of oral health status. Dietary advice to patientsshould be positive and personalized if possible and can be in line with general health. This paper is intended toprovide an overview of management of dietary advice for patients with dental caries, periodontal disease and oralsurgery which could be implemented in dental practice setting. The appropriate and specified nutrition advice canhelp patient recover from dental disease and achieved the best result of dental treatment and prevention.